Synergy of Leadership, Competency, and Culture in Building High-Performance Teams - Djoko Setyo Widodo (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Building high-performance teams is essential dynamic and competitive organizational environment. Success in teams is shaped not only by the capabilities of individual members but also by effective leadership and a supportive organizational culture. This study aims to explore the interplay between leadership, competence, and organizational culture in fostering high-performance teams. Specifically, it examines how these three factors interact and collectively influence team effectiveness within organizations. Adopting a literature review approach, the study analyzes a range of relevant scholarly sources to develop a comprehensive understanding of the topic. Findings suggest that transformational leadership plays a pivotal role in inspiring and motivating team members to deliver optimal performance. In addition, individual competence encompassing both technical skills and soft skills provides a solid foundation for team success. A collaborative and innovative organizational culture further enhances synergy, enabling teams to excel in complex and changing conditions. The study concludes that the integration of leadership, competence, and organizational culture is vital for creating high-performance teams and ensuring sustainable organizational growth.